Fenología de compuestas herbáceas (Compositae) en el Parque del Este, Costa Rica - Valerio, Carlos E.; Moreira, Ileana (Revista de Biología Tropical, 1986)
In the herbaceous community of Parque del Este, in the Central Valley, Costa Rica, the Compositae represent nearly 30% of the total species. Phenological data were collected in a two-year period in eleven of the common species, showing that one is a rainy-season bloomer (Coniza apurensis), two are active all year (Calinsoga parviflora and Calyptocarpus vialis) and in nine, reproduction is concentrated in the dry season (fig. 1). This preference for dry weather might be related with mean s for seed dispersal, mainly by anemochory and ectozoochory.